Dysregulated Expression of miR-146a and Its Associated Immune Effectors in Peripheral Blood Mononuclear Cells of Esophageal Carcinoma Patients. (17th February 2022) - Nariman-Saleh-Fam, Ziba; Mansoori, Yaser; Saadatian, Zahra; Tavakkoly-Bazzaz, Javad; Daraei, Abdolreza; Zununi Vahed, Sepideh; Mahmoodzadeh, Habibollah; Bastami, Milad
ABSTRACT: Esophageal cancer is one of the least studied aggressive tumors, with the squamous cell carcinoma (ESCC) being the most frequent histological type around the world. Growing evidence has shown that the abnormal expression of microRNAs (miRNAs) in peripheral blood mononuclear cells (PBMCs) is closely related to the pathogenesis of cancers. MiR-146a is a crucial regulator of inflammatory cascades. There is currently no data available regarding the possible role of miR-146a in PBMCs of ESCC patients. We evaluated the expression of miR-146a, as well as its target genes (IRAK1 and TRAF6) and its associated immune effectors (NF-κB1, IL1B, and IL6) in PBMCs of 40 ESCC patients and 50 control subjects. The geometric mean expression of five transcripts was used for normalizing expressions. The PBMC level of miR-146a, as measured by RT-qPCR, was upregulated, whereas levels of its target genes, IRAK1 and TRAF6, were downregulated in ESCC patients. NF-κB1 and IL6 was downregulated in PBMCs of ESCC patients. There was no difference in terms of the IL1B level between patients and the control group. Logistic regression and receiver operating characteristic curve analysis suggested that a model with PBMC levels of either NF-κB1+ IL6 or NF-κB1+ miR-146a as predictors may discriminate ESCC patients from subjects of the control group. Our findings, in the context of the current literature, may suggest a possible downregulatory mechanism of immune responses in PBMCs of ESCC patients.